2013
DOI: 10.4049/jimmunol.1200873
|View full text |Cite
|
Sign up to set email alerts
|

Ly49Q Positively Regulates Type I IFN Production by Plasmacytoid Dendritic Cells in an Immunoreceptor Tyrosine–Based Inhibitory Motif–Dependent Manner

Abstract: Plasmacytoid dendritic cells (pDC) are the major producers of type I IFN during the initial immune response to viral infection. Ly49Q, a C-type lectin-like receptor specific for MHC-I, possesses a cytoplasmic ITIM and is highly expressed on murine pDC. Using Ly49Q-deficient mice, we show that, regardless of strain background, this receptor is required for maximum IFN-α production by pDC. Furthermore, Ly49Q expression on pDC, but not myeloid dendritic cells, is necessary for optimal IL-12 secretion, MHC-II expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…pDCs are specialized in direct virus recognition and secretion of large amounts of IFN-I early during infection (111, 112). Using a gene knock-out mouse model, we have shown that Ly49Q, despite being an inhibitory receptor, positively regulates Toll-like receptor (TLR)-mediated IFN-I production by pDCs (113, 114). In mice lacking Ly49Q, both TLR7 and TLR9-mediated IFN-I production by pDCs is attenuated (113).…”
Section: Ly49 Expression and Function On Cells Of The Myeloid Lineagementioning
confidence: 99%
See 2 more Smart Citations
“…pDCs are specialized in direct virus recognition and secretion of large amounts of IFN-I early during infection (111, 112). Using a gene knock-out mouse model, we have shown that Ly49Q, despite being an inhibitory receptor, positively regulates Toll-like receptor (TLR)-mediated IFN-I production by pDCs (113, 114). In mice lacking Ly49Q, both TLR7 and TLR9-mediated IFN-I production by pDCs is attenuated (113).…”
Section: Ly49 Expression and Function On Cells Of The Myeloid Lineagementioning
confidence: 99%
“…In mice lacking Ly49Q, both TLR7 and TLR9-mediated IFN-I production by pDCs is attenuated (113). Although the precise mechanism of this positive regulation is not known, it is Ly49Q ITIM-dependent but may not involve interaction with the SHP-1/2 phosphatases (114). One of the possible mechanisms could be a cooperative activation of interferon regulatory factors (IRF) in conjunction with TLR-mediated downstream signals, leading to enhanced IFN-I production.…”
Section: Ly49 Expression and Function On Cells Of The Myeloid Lineagementioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, Ly49Q is also involved in the regulation of IFN-I production by enhancing Toll-like receptor-9 (Tlr9)-mediated signaling in pDCs (Rahim et al, 2013). On pDCs, Ly49Q was shown to bind H-2K b , a classical MHC class I molecule (Tai et al, 2007), which enhances pDC function (Tai et al, 2008).…”
Section: Transciption and Growth Factors Driving Differentiation Of Pdcsmentioning
confidence: 99%
“…This receptor enhanced, rather than inhibited, TLR9-mediated signaling events in plasmacytoid dendritic cells. The positive effect depended on the Ly49Q ITIM, but did not require SHP-1, SHP-2, or SHIP phosphatase activity (34). Thus ITIM-bearing Ly49 receptors can improve cellular activation.…”
Section: Arming Nk Cellsmentioning
confidence: 99%